Analytical Techniques for Phytochemical Characterization of Selected Medicinal Plants - Dhungana, Prem Prasad (Journal of Contemporary Review, 2024)
Phytochemical study helps to identify bioactive compounds in medicinal plants, mainly alkaloids, flavonoids, tannins, terpenoids, and phenolics, which are known for their therapeutic potential. Traditional extraction methods such as maceration and Soxhlet remain useful, but modern green approaches like supercritical fluid extraction and ultrasound-assisted extraction offer higher efficiency and sustainability. For compound identification, classical methods including Thin Layer Chromatography (TLC), High Performance Liquid Chromatography (HPLC), Gas Chromatography-Mass Spectrometry (GC-MS), and Fourier Transform Infrared Spectroscopy (FTIR) remain reliable. Latest advance, such as Nuclear Magnetic Resonance (NMR), Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS), metabolomics, and machine learning–assisted spectral analysis, have further enhanced accuracy in profile complex plant metabolites. Together, these integrated methods strengthen quality control, ensure standardization, and accelerate natural product–based drug discovery. Phytochemical analysis thus continues to bridge traditional plant knowledge with modern pharmaceutical applications.